2017
DOI: 10.15578/iaj.12.2.2017.53-58
|View full text |Cite
|
Sign up to set email alerts
|

COMPENSATORY GROWTH OF Oreochromis niloticus SELECTED STRAIN FROM BOGOR, WEST JAVA

Abstract: In efficient feed management strategy in aquaculture will increase the fish production cost. One of the most effective strategies to solve this problem is through a better understanding of the compensatory growth of cultured fish. O. niloticus BEST tilapia strain (total length: 7.23 ± 0.11 cm mean ± SD; Body weight: 7.04 ± 0.08 g mean ± SD) were reared in aquariums at 26.3 ± 1.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…When re-feeding is done, energy comes from feed protein for growth (Khotimah, 2009). Prakoso and Kurniawan (2017) reported that best tilapia fasted for 7-14 days experienced a decrease in body weight, however, after refeeding 42 days at the end of the experiment, it showed that the fish biomass that was fed restricted for 7 days showed a higher value than control.…”
Section: Growth Performancementioning
confidence: 96%
“…When re-feeding is done, energy comes from feed protein for growth (Khotimah, 2009). Prakoso and Kurniawan (2017) reported that best tilapia fasted for 7-14 days experienced a decrease in body weight, however, after refeeding 42 days at the end of the experiment, it showed that the fish biomass that was fed restricted for 7 days showed a higher value than control.…”
Section: Growth Performancementioning
confidence: 96%
“…In addition, due to the use of different types of chemicals includes heavy metals and antibiotics in fish feed deflating the nutritious quality, effects on fish growth and diseases resistance capacities, thus raised potential risk on human health by consumption [10,23]. In aquaculture, feeding cost is responsible for over 70 percent of the production cost thus inefficient feed management increase the fish production cost [20,24,25]. Balanced feed is essential for better fish growth, reproduction, and other physiological functions [4,25,26].…”
Section: Introductionmentioning
confidence: 99%